Educational Project Management and Resource Provisioning System–Project-Based Learning on a Scale - Ajanovski, Vangel (Association for the Advancement of Computing in Education (AACE), 2021)
Enabling students to work on realistic projects is important as they open the possibility to handle real problems and scenarios that can not be found inside the classroom and laboratory setting. Project-based courses simulate the reality of the business work place, with all the activities, interactions and tools. One of the implications is that students will also need a complex of tools and resources, to use in their everyday work. Allowing the students to self-organize on which tools to use and how, may be feasible for some courses, but may not be suitable for courses where student’s need to follow a process and will not be feasible in large courses, as the teacher will have to access and monitor activities across hundreds, if not thousands, tools and different organization schemes. On the other hand, creation of many identical organizational templates and schemes for students to use in many different tools can be bothersome, repetitive and over-burdening for many teachers. This paper presents the development and introduction of a specialized system that will sit in the middle of many needed tools, and will enable management of the integration of such tools to student project phases and activities, coordination of resource provisioning for students and integral monitoring of the project work across all projects in a course. The system is available as a FLOSS (free/libre open-source software) for the benefit of the wider academic community.